Analysis of Chemical Elements in Major Perlis' Agriculture Residue - Suhardy, Daud; Mohd Nazry, Salleh; Farizul Hafiz, Kasim; Saiful Azhar, Saad (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2008)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 9th - 10th December 2006 at Putra Palace Hotel, Kangar, Perlis.